A Path Analysis: Study of Correlation Between Noise Intensity and Quality of Life of Workers In Textile Industry. (December 2019) - Sumardiyono,; Probandari, Ari; Hartono,; Wijayanti, Reni
Abstract: Noise intensity is a dangerous stressor in the working environment of the textile industry that can have an impact on the decrease in hearing loss of workers. The decrease in hearing loss will disrupt the workers' activities in their daily work. Textile industry workers exposed to noise while working every day will potentially be affected by a decrease in hearing loss. Activities that are constantly exposed to noise intensity can also result in a decrease in the quality of workers' life. This research was conducted to prove the correlation between noise intensity and quality of life through hearing loss using path analysis. Path analysis can explain the correlation between variables indirectly. The research method was used namely analytic survey with the cross-sectional design. The population of the study was workers in 5 textile industries in Central Java Province, Indonesia. The number of subjects was determined based on purposive sampling, each industry was 40 people thus, and the total number was 200 people. The correlation was included independent variables namely noise intensity, work period and age; the mediator variable was a loss of hearing loss, and the dependent variable was quality of life. Path analysis was used as the statistical analysis with Stata 13 software at a significance level of 5%. The research results showed that there was a direct correlation between hearing loss and decreased the quality of life of workers (p = 0.026). The decrease in the quality of workers' life was also influenced indirectly by noise intensity (p = 0.000) and age (0.012). The working period did not affect the decrease in quality of life (p = 0.210). Increased noise intensity can reduce hearing loss that decreases the quality of life.